The advanced characterization, post-irradiation examination, and materials informatics for the development of ultra high-burnup annular U-10Zr metallic fuel - Yao, Tiankai; Bachhav, Mukesh; Di Lemma, Fidelma G.; Xu, Fei; Teng, Fei; Murray, Daniel J.; Benson, Michael T.; Capriotti, Luca (Frontiers in Nuclear Engineering, 2023)
U-Zr-based metallic fuel is a promising fuel candidate for Gen Ⅳ fast spectrum reactors. Through a historical irradiation campaign, the sodium thermal boned U-10Zr design can achieve a burnup of 10% fissions per initial heavy metal atom (FIMA), newer fuel designs are pushing the burn-up limit to 20% or even 30% FIMA. To achieve the higher burnup and eliminate the pyrophoric sodium simultaneously, a prototypical annular fuel has been designed, fabricated, cladded with HT-9 in the Materials & Fuels Complex, and irradiated in the Advanced Test Reactors of Idaho National Laboratory (INL) to a peak burnup of 3.3% FIMA. During irradiation, the mechanical contact between fuel and cladding acts as heat dissipation paths. The irradiation lasted for 132 days in the reactor. Recently, both the achieved fresh and irradiated fuel samples were characterized using advanced characterization methods developed in the Irradiated Materials Characterization Laboratory of INL. This paper showcases the application of advanced characterization and materials informatics to study the irradiation effects on metallic fuel. Future work will focus on further implementation of advanced characterization and statistical data mining to help better fuel performance modeling and support U-Zr-based metallic fuel qualification for advanced reactors.